Kisaran Service Per Conception (S/C) Sapi Peranakan Ongole (PO) di Desa Srimulyo Kecamatan Kalirejo Kabupaten Lampung Tengah - Ferry Hernanto (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2020)
The research of Service per Conception in Ongole Cross-breed cows in Srimulyo village, Kalirejo District, Central Lampung Regency was conducted in January 2019 until February 2019. The material submitted in the reseach are 200 Ongole Cross-breed cows. The variable research is Service per Conception (S/C). The method used in this research is to collect primary and secondary data. Analysis data used descriptive and quantitative analysis. The results can be seen that the Service per Conception (S/C) of Ongole Cross-breed cows in Srimulyo village ranged from 2.36-2.67. Keywords: Ongole Cross-breed Cows, Service per Conception, Srimulyo Village, Value